A produção de daguerreótipos no Rio de Janeiro (1840-1850) - Silva, Shirley (2016)
This research aims to identify and to analyze the specificities of the production of daguerreotypes in Rio de Janeiro between 1840 and 1850. The daguerreotype was the first photographic process recognized and patented by the French government in August 1839. In Brazil, the abbot Louis Compte presented it in January 1840 in Rio de Janeiro city, with the attendance of the future emperor, d. Pedro II. To develop the research we have used as documents advertisements made by daguerreotypers in newspapers circulating at that time at the Brazilian Court and the manual for the production of daguerreotypes. From the information contained in the advertisements, we have established categories aiming to systematize the data, as follows: teachers, trade, frame, accessories, shapes, time, hours, color, detail and innovations. In this manner, it was possible to compare general information concerning the daguerreotypes production and the particularities presented by the photographers, connecting data and making it possible to map the process of knowledge from this period